Monitor IPCLNs Regarding Nurses' Performance in Preventing Nosocomial Infections - Iskandar, Rahayu; Nur, Wahida (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Jenderal Achmad Yani Yogyakarta, 2023)
Backgroud: In the professional practice of nursing, supervision is the process that provides nurses with the many tools they need to carry out their work in order to achieve the goals of the organization. Nursing supervision is part of nursing management, which focuses on nurses' competencies and skills in the delivery of nursing care to patients and families. In an effort to improve service quality and prevent hospital-acquired infections, supervision is critical. Objective: This study aims to determine the correlation between implementation of supervision and performance of implementing nurses in preventing nosocomial infections in regional public hospital Nyi Ageng Serang Kulon Progo. Methods: Correlational descriptive research with cross-sectional approach. The population in this study is all practicing nurses in the inpatient ward class III in regional public hospital Nyi Ageng Serang Kulon Progo. Total sampling is used as the data collection method. Result: The results show that most of the nurses perceived the implementation of supervision by Infection Prevention and Control Nurse (IPCLN) in the category as much 27 (69.2%) nurses. The performance of implementing nurses in preventing the incidence of nosocomial infections in the less optimal category is 18 (46.2%) nurses. Bivariate test results obtained p-value=0.202 by r=0.200 Summary: There is no correlation between the implementation of supervision and the performance of nursing staff in the prevention of nosocomial infections.